Find the value of the exponent c that makes the second expression equivalent to the first expression where x ≥ 0 and y ≥ 0.

Question

Find the value of the exponent c that makes the second expression equivalent to the first expression where x ≥ 0 and y ≥ 0.

in progress 0
Mia 2 weeks 2022-01-08T06:31:25+00:00 2 Answers 0 views 0

Answers ( )

    0
    2022-01-08T06:32:34+00:00

    Answer:

    1. a=2 b=4

    2.c=4

    3. b

    Step-by-step explanation:

    the entire slide, your welcome.

    0
    2022-01-08T06:32:34+00:00

    Answer:

    c=4

    Step-by-step explanation:

    3^4/4.2^2/4.x^6/4.y^8/4=2^2/4.3^4/4.x^(c+2)/4.y^8/2

    3.2^1/2.x^3/2.y^2=2^1/2.3.x^(c+2)/4.y^2

    x^3/2=x^(c+2)/4  

    3/2=c+2/4

    3.4/2=c+2

    6=c+2

    c=4

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )